PERAN HUMAS DALAM PENGELOLAAN INFORMASI PUBLIK MELALUI APLIKASI SMILE PUSKESAD - Ni Putu Arianti; Ni Putu Yunita Anggreswari; Ni Nyoman Sri Wisudawati; Ni Putu Intan Permatasari (Bajang Institute, 2025)
This study aims to analyze the role of public relations in managing public information through the SMILE Puskesad application at Tk. II Udayana Hospital as part of efforts to enhance transparency and improve the quality of health services. Employing a qualitative method with a case study approach, data were collected through in-depth interviews, field observations, documentation, and a review of relevant literature. The findings indicate that information management is carried out through monitoring patient satisfaction survey data, verifying and classifying reports, formulating information messages, and coordinating follow-up actions with related service units. Public relations also play a role in educating the public on the use of the application, although several challenges persist, including low levels of digital literacy among patients, limited internal socialization, and suboptimal digital communication strategies. Tk. II Udayana Hospital addresses these obstacles by strengthening coordination, utilizing digital media, and reinforcing the role of public relations as an information bridge between the hospital and the community. More specifically, the study demonstrates that optimizing the role of public relations directly contributes to the effectiveness of public information delivery through the SMILE Puskesad application, resulting in information that is more accurate, accessible, and capable of increasing public participation in patient satisfaction surveys